Managing multidimensional knowledge assets: HR configurations in professional service firms. (8th July 2012) - Swart, Juani; Kinnie, Nicholas
<x xml:space="preserve">Abstract</x> The purpose of this article is to illustrate empirically how HR practices are configured to manage multidimensional knowledge assets. It contributes directly to the configurational approaches to HRM by identifying HRM systems that are used to manage various types of knowledge assets. First, we develop a framework from theory to categorise knowledge assets into human (industry and firm specific), social (entrepreneurial and co‐operative) and organisational capital (mechanistic and organic). Within this framework, we draw on data gathered in the 12 professional services firms to understand how HR practices enable the management of each knowledge asset. We identify two configurations of HR practices (organisationally and professionally focused). These configurations do not exist in isolation but are used simultaneously by organisations via either a targeted (different practices in different parts of the organisation) or a temporally segregated way (different practices for the same group of employees over time).